Faktor-Faktor yang Mempengaruhi Keputusan Mahasiswa Memilih Perguruan Tinggi Swasta (Kasus pada STIM YKPN Yogyakarta) - Boy Setiawan; Retno Hartati (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2021)
Abstract Thousands of private universities (PTS) in Indonesia can be selected prospective new students to continue their education. In Yogyakarta there are 106 PTS that compete with each other by improving the quality of education and always trying to correct every deficiency in order to excel and can attract prospective students. This study analyzed product, price, place, promotion, people, process, and physical evidence on students' decisions in choosing PTS, case studies at STIM YKPN Yogyakarta. The population in this study is active students of STIM YKPN Yogyakarta odd semester of Academy Year 2020/2021. Sampling using non probability sampling technique with purposive sampling method. A total of 280 students participated in the study. The tests used are validity test, reliability test, normality test, multicolinearity test, heterokedastisity test, multiple linear regression test, t test, F test, and determination coefficient test. The results of the study stated that partially variable product, price, promotion, process, and physical evidence had a positive and significant effect on the decision of students choosing significantly affect the decision of students choosing a PTS, case studies at STIM YKPN in Yogyakarta.